(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
As in the findings of earlier studies (e.g., Alamu, 2010; Cross, 2009; Thompson, 1984; Whitehouse, 2003), teachers in this study were found to hold beliefs about the nature of mathematics, mathematics learning, and mathematics teaching that reflect a combination of traditional and constructivist perspectives to varying degrees.